Elaeagnus angustifolia Plant Extract Inhibits Angiogenesis and Downgrades Cell Invasion of Human Oral Cancer Cells via Erk1/Erk2 Inactivation. (17th February 2018) - Saleh, Alaaeldin I.; Mohamed, Islam; Mohamed, Ahmed A.; Abdelkader, Mennatallah; Yalcin, Huseyin C.; Aboulkassim, Tahar; Batist, Gerald; Yasmeen, Amber; Moustafa, Ala-Eddin Al
ABSTRACT: Oral cancer is a common malignancy in both men and women worldwide; this cancer is characterized by a marked propensity for invasion and spreading to local lymph nodes. On the other hand, Elaeagnus angustifolia ( EA ) is a medicinal plant that has been used for centuries for treating many human diseases in the Middle East. However, the effect of EA plant extract on human cancers especially oral has not been investigated yet. Thus, first we examined the outcome of EA flower extract on angiogenesis, using the chorioallantoic membrane (CAM) of the chicken embryo; we found that EA extract reduces blood vessel development of the CAM. Then, we investigated the effect of EA flower extract on selected parameters in FaDu and SCC25 oral cancer cell lines. Our results show that EA extract inhibits cell proliferation and colony formation, in addition to the initiation of S cell cycle arrest and reduction of G1/G2 phase. In parallel, EA extract provokes differentiation to an epithelial phenotype "mesenchymal-to-epithelial transition: MET" which is the opposite of "epithelial-to-mesenchymal transition, EMT": an important event in cell invasion and metastasis. Thus, EA plant extract causes a dramatic decrease in cell invasion and motility abilities of FaDu and SCC25 cancer cells in comparison with their controls. These changes are accompanied by an upregulation of E-cadherin expression. The molecular pathway analysis of the EA flower extract reveals that it can inhibit the phosphorylation of Erk1/Erk2, which could be behind the inhibition of angiogenesis, the initiation of MET event, and the overexpression of E-cadherin. Our findings indicate that EA plant extract can reduce human oral cancer progression by the inhibition of angiogenesis and cell invasion via Erk1/Erk2 signaling pathways.